History of motion pictures film research & learning - A2ZCDS.com (Firm) (Orlando, FL. : A2ZCDS.com, 2005)
"Witness some of the earliest educational films made in the United States and examine their relevance to the present-day scenario. Learn how producers made films, which helped schools in selecting the most appropriate titles for students. Observe how sound was added to motion pictures in the '30s."--Container.
Choosing a classroom film (1963) / McGraw-Hill Films (19:38) -- Film research and learning (1956) / Wittich (Walter Arno) (13:04) -- How to use a classroom film (1963) / Centron Productions (14:21) -- Making films that teach (1954) / Encyclopaedia Britannica Films (18:12) -- The unique contribution (1959) / Encyclopaedia Films (29:04) -- Facts about film (n.d.) / Phototronics (10:02) -- Photography (1946) / Holmes (Burton) Films (09:43)
DVD format ; NTSC, all region.
DVD-ROM ; requires DVD-ROM drive.
Keywords: Motion pictures in education -- United States -- History